Octreotide inhibits secretion of IGF-1 from orbital fibroblasts in patients with thyroid-associated ophthalmopathy via inhibition of the NF-κB pathway - Kim, Sung Eun (PLoS One, 2021)
PURPOSE: We investigated the effect of octreotide, a long-acting somatostatin (SST) analogue, on IGF-1 secretion and its possible mechanism of action in orbital fibroblasts (OFs) from patients with thyroid-associated ophthalmopathy (TAO). MATERIALS AND METHODS: OFs were isolated from the orbital fat of patients with TAO or healthy individuals. The expression level of insulin-like growth factor (IGF)-1, at the protein and mRNA level, was determined with ELISA and quantitative RT-PCR, respectively. The expression pattern of somatostatin receptor (SSTR) 2, which has the highest affinity for octreotide, was examined by flow cytometry. The activity of NF-κB pathway was determined by examining the levels of phosphorylation of IKKα/β and p65, and degradation of IκB via western blot analysis, and by measuring the activity of NF-kB-dependent luciferase via transfection with plasmids containing luciferase and NF-κB binding site. RESULTS: OFs from patients with TAO showed significantly higher levels of IGF-1 secretion and NF-κB activity even in the absence of stimulation, compared to those from controls. Treatment with octreotide reduced the level of IGF-1 secretion in OFs from patients with TAO, but not in OFs from controls. OFs from patients with TAO expressed higher levels of SSTR2 on the cell surface, compared to controls. In addition, the expression of IGF-1 at the protein and mRNA level was dependent on the activity of NF-κB pathway in OFs from patients with TAO. Furthermore, treatment with octreotide reduced on the activity of NF-κB pathway in OFs from patients with TAO. CONCLUSION: OFs from patients with TAO showed significantly higher levels of IGF-1 secretion via up-regulation of NF-κB activity. Treatment with octreotide inhibited the secretion of IGF-1 by reducing the NF-κB pathway in OFs, which expressed higher levels of SSRT2 on the cell surface, from patients with TAO.